Proyecto de factibilidad de la creación de una microempresa dedicada a la elaboración y distribución de uniformes de trabajo en la cuidad de Cayambe, provincia de Pichincha - Tutillo Iguamba, Blanca Cecilia (2015)
The main purpose of this project is the study to create a new small enterprise that can elaborate and distribute working uniforms in Cayambe City, Pichincha Province; this has motivated the analysis of all the aspects related to this research. To carry out this research project Different methods were used, such as the scientific method, deductive method, inductive method and analytic method. Furthermore there were techniques like observation, interviews and surveys that were applied to the study’s population. The market research was done in Cayambe City with 335 enterprises that were the sample and we found out that 222 of them utilize working uniforms, then the results are the following: there is a potential demand of 669 862 of uniforms that correspond to a population of 2008 enterprises and the growth rate is 4,5%, the actual demand is 442.109 uniforms and the effective demand is 424.203 uniforms. The actual supply is 18 950 uniforms and the unsatisfied demand is 404 268 uniforms, in consequence it was determined that this project is viable. In the technique study it was determined the macro and micro localization, size, the project’s structure, process diagrams and technique requirements such as equipment and furniture. Administrative study was held to constitute the microenterprise as a limited liability company. The organizational structure with hierarchical levels of different areas was represented through charts detailing the roles of each person of the microenterprise through functions manuals. Financial study was presented, which shows the investment and financing by loan and contribution of the partners, these are requirements for launching the project. The financial evaluation presents the following results: positive NPV (Net Present Value) 261 273, 72, IRR (Intern Return Rate) 54,30; time to recover the investment would be 1 years, 5 months and 10 days, the values of sensitivity to a 21% increase is 0,99, and the values of sensitivity to a 15.5% decrease is 0.99. Among the most relevant conclusions and recommendations we have found out that the project implementation is recommended thanks to the results obtained through financial analysis